The Effectiveness of the Problem Based Learning Model in Improving Collaborative Capabilities and Student Learning Outcomes in Class XI SMA: Efektifitas Model Problem Based Learning dalam Meningkatkan Kemampuan Kolaboratif dan Hasil Belajar Peserta Didik di SMA Kelas XI - 'Aini, Darista Nur; Saptasari, Murni; Hadi, Abdul Nurul (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
One of the skills that must be possessed by students in the 21st century is collaborative ability. Collaborative skills are abilities possessed by individuals in the form of groups to exchange thoughts or ideas and work together to achieve the expected goals. Increasing collaborative skills in students has a positive impact, namely producing more knowledge than just completing work independently and students can exchange ideas to be able to solve problems encountered in the learning process obtained.The efforts made in this study by applying the problem based learning (PBL) learning model to be able to improve collaborative abilities and learning outcomes learners. The use of the PBL learning model can improve scientific attitudes and student learning outcomes. The PBL model can improve learning outcomes and students' communication skills. The problem-based learning model can assist teaching staff in undergoing the learning process because it can improve student learning outcomes. Based on the background that has been formulated, the purpose of conducting this research is to determine the effectiveness of the PBL model in improving collaborative abilities and student learning outcomes in class XI reproductive system material.